Effect of desiccation tolerance on seed germination and vigor of hybrid maize (Zea mays L.) - E. Rezvani; F. Ghaderifar; A. Hamidi; E. Soltani (علوم و فناوری بذر ایران)
In order to study the effect of desiccation tolerance on seed germination and vigor of hybrid maize, a field experiment was conducted using five sowing dates in three replications. Experiments were conducted in a completely randomized design in Karaj, Iran. Sampling from female rows (B73 Inbred line) was started right after pollination in a weekly scale. The harvested hybrid seeds were dried in open air conditions. Changes in seed growth and development were evaluated from 20 days after flowering and laboratory tests were performed on fresh and dried seed samples of each developmental stages. The results showed that the effects of sowing dates on normal seedling percentage, mean germination time) and seedling length was significant. The 4th sowing date had the highest normal seedling and seed vigor. Seed filling rate (3.7-9.2 mg/gram) and moisture content reduction (0.63 -1.06 percent/day) was different, depends on the sowing date and temperature of seed developmental period. It is observed that the developing seeds that dried before standard germination test, started to germinate very sooner (20-30 DAF on basis of sowing date) than fresh seeds (that start 30-50 DAF). Dried seeds reached meaningfully sooner to the highest normal seedlings percentage (30-60 DAF). When the desiccation started without hot temperature stress in third and fourth sowing dates, desiccation tolerance completed sooner. So the seeds reach to the highest percentage of normal seedling very soon, after drying. The evaluation of mean germination time and seedling length, as indicators of seed vigor showed that dried seeds reach to maximum germination rate and seedling length sooner than fresh seeds. The changes trend in these indicators was similar to changes in normal seedling percentage. It was concluded that appropriate temperature (lower than 35ºC) in desiccation period, especially at the beginning stages, results in fast extension of desiccation tolerance among the seeds and enhancing the seed quality after drying.